2017
DOI: 10.1262/jrd.2016-183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of investigational kisspeptin/metastin analog, TAK-683, on luteinizing hormone secretion at different stages of the luteal phase in goats

Abstract: This study aimed to examine the response of luteinizing hormone (LH) secretion and ovarian steroid profile to TAK-683, an investigational metastin/kisspeptin analog, through treatment during different stages of the luteal phase in goats. Nine cycling Shiba goats (4.4 ± 2.3 years old) were assigned to early luteal phase (ELP, n = 4), mid-luteal phase (MLP, n = 4), and control (n = 5) groups. The ELP and MLP groups were administered 50 µg of TAK-683 intravenously on either day 5 or between days 7–14 after ovulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Kisspeptin has also been proposed to act as a bridge between energy homeostasis and reproduction [14]. To this regard, kisspeptin and its analog TAK-683 have been reported to stimulate luteinizing hormone release in vivo [15,16]. Moreover, central, but not peripheral, injection of kisspeptin-10 was found to decrease food intake in overnight fasted mice [5].…”
Section: Introductionmentioning
confidence: 99%
“…Kisspeptin has also been proposed to act as a bridge between energy homeostasis and reproduction [14]. To this regard, kisspeptin and its analog TAK-683 have been reported to stimulate luteinizing hormone release in vivo [15,16]. Moreover, central, but not peripheral, injection of kisspeptin-10 was found to decrease food intake in overnight fasted mice [5].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have indicated that the potential of a bolus administration of TAK-683 to GnRH/LH secretion differs between the ovariectomized [ 5 , 7 ] and ovary-intact [ 8 , 9 ] goats. The secretory pattern of GnRH/LH after a single intravenous injection of 50 μg of TAK-683 was shown to be characterized by episodic increases of relatively small amplitude in orchidectomized [ 5 ] and ovariectomized goats [ 5 , 7 ].…”
mentioning
confidence: 99%
“…The timing of oestradiol changes associated with TAK683 injection depended upon the phase of oestrous cycle at the time of treatment, but ovulation was induced in five of five does and four of five does when TAK683 treatment was initiated in the follicular and luteal phase of the oestrous cycle, respectively. The magnitude of LH release induced by TAK683 was greater when does were treated in the follicular phase (Endo et al, 2015) than in the luteal phase (Endo et al, 2015;Rahayu et al, 2017).…”
Section: Use Of Kisspeptin and Kisspeptin Analogues For Pharmacologicmentioning
confidence: 88%